Analisis Faktor-faktor Yang Mempengaruhi Minat Berwirausaha Mahasiswa dalam Bisnis Islam Melalui Motivasi - Sri Rezeki Widya Ritonga; Tuti Anggraini; Zuhrinal M. Nawawi (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to determine the effect of entrepreneurial knowledge, self-efficacy, and family environment on students' entrepreneurial interest through motivation. This study uses quantitative methods by questionnaires distributed to students of the Potensi Utama University as many as 90 respondents with the sampling technique. The data obtained were then processed using SPSS Version-23, then analyzed using path analysis. The analysis used includes the validity and reliability test of the instrument, the classical assumption test which includes the normality test, the multicollinearity test, and the heteroscedasticity test, as well as the statistical test which provides for the determination test, partial test (t-test), and simultaneous test (f-test). The results of this study indicate that entrepreneurial knowledge partially affects motivation, self-efficacy partially affects motivation, family environment partially does not affect motivation, and motivation affects student entrepreneurial interest. Entrepreneurship knowledge partially affects Student Entrepreneurial Interest, Self Efficacy partially affects Student Entrepreneurial Interest, and Family Environment partially does not affect Student Entrepreneurial Interest. From the significance test results, it was found that the family environment had no significant effect on Student Entrepreneurial Interest through Motivation. Meanwhile, the variables of Entrepreneurship Knowledge and Self-Efficacy have a significant effect on Student Entrepreneurial Interest through Motivation.